Embedded nanograting-based waveplates for polarization control in integrated photonic circuits - Lammers, Kim; Ehrhardt, Max; Malendevych, Teodor; Xu, Xiaoyu; Vetter, Christian; Alberucci, Alessandro; Szameit, Alexander; Nolte, Stefan (Optical Materials Express, 2019)
Femtosecond laser direct writing (FLDW) enables precise three-dimensional structuring of transparent host materials such as fused silica. With this technique, reliable integrated optical circuits can be written, which are also a possible candidate for future quantum technologies. We demonstrate the manufacturing of integrated waveplates with arbitrary orientations and various phase delays by combining embedded birefringent nanograting structures and FLDW waveguides in fused silica glass. These waveplates can be used both for classical applications and for quantum gates.
CRIS-Team Scopus Importer:2023-04-20